Determination of Cardinal Directions and the Gesture of Orant Določitev strani neba in drža oranta - Mareš, Jiří J. (Studia mythologica Slavica, 2012)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The paper is devoted to an interesting question closely related to the orientations of graves and archaeoastronomical objects in Central Europe, namely, to the determination of cardinal directions during the period ranging from Hallstatt era to Early Middle Ages. Using exhaustive procedure, we have shown that the most likely method for the determination of cardinal directions was that based on the horizontal observation of Sun sets and rises. The intrinsic part of this method is the angle–halving which can be performed either with or without instruments. Reconstruction of the later possibility, supported also by the experimental verification, led us to the conclusion that the hypothetical attitude used for the angle–halving is to be practically identical with the so called gesture of orant, usually interpreted as a posture of early Christian prayer. Interpreting then the burial orientation as a charitable gift, we further claim that the gesture of orant, being originally used for orientation in the unknown terrain, might develop quite naturally into a ritual gesture. Cultural, historical and technical arguments in favour to this idea are given.